(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Service marketing refers to the marketing of intangible and perishable services. It is a new phenomenon in the field of marketing and started in the 1980s when there was a debate about whether the services were to be marketed separately or not. Services were considered as totally different from the products, so a separate discipline of service marketing was initiated. The service marketing mix is an extension of the product marketing mix, and it will have 3 additional P’s along with the 4 P’s of the product marketing mix. This paper discusses the 7 P’s that are required for service marketing.